Intergenomic epistasis for fitness: within-population interactions between cytoplasmic and nuclear genes in Drosophila melanogaster. - Dowling, D.K.; Friberg, U.; Hailer, F.; Arnqvist, G. (Genetics, 2007)
The symbiotic relationship between the mitochondrial and nuclear genomes coordinates metabolic energy production and is fundamental to life among eukaryotes. Consequently, there is potential for strong selection to shape interactions between these two genomes. Substantial research attention has focused on the possibility that within-population sequence polymorphism in mitochondrial DNA (mtDNA) is maintained by mitonuclear fitness interactions. Early theory predicted that selection will often eliminate mitochondrial polymorphisms. However, recent models demonstrate that intergenomic interactions can promote the maintenance of polymorphism, especially if the nuclear genes involved are linked to the X chromosome. Most empirical studies to date that have assessed cytonuclear fitness interactions have studied variation across populations and it is still unclear how general and strong such interactions are within populations. We experimentally tested for cytonuclear interactions within a laboratory population of Drosophila melanogaster using 25 randomly sampled cytoplasmic genomes, expressed in three different haploid nuclear genetic backgrounds, while eliminating confounding effects of intracellular bacteria (e.g., Wolbachia). We found sizable cytonuclear fitness interactions within this population and present limited evidence suggesting that these effects were sex specific. Moreover, the relative fitness of cytonuclear genotypes was environment specific. Sequencing of mtDNA (2752 bp) revealed polymorphism within the population, suggesting that the observed cytoplasmic genetic effects may be mitochondrial in origin.